The Role of Digital Social Entrepreneurship in Driving Green Economy and SDGs - Mustaqim, Dede Al (Economics and Business Solutions Journal, 2024)
Environmental conservation and sustainable development are gaining increasing attention globally. Environmental problems such as climate change, environmental degradation, and resource crises are the focus of the attention of various parties, including the community, government, and private sector. This research aims to explore the role of the digital ecosystem and social entrepreneurship practices among the youth of Lintang Nuswantara Cirebon in supporting the Green Economy and Sustainable Development Goals. A qualitative approach with a case study was used to understand the role of this ecosystem. The results of this study show that excellent programs such as Youth Social Care Camp (YSCC), Lintang Muda Mengabdi (LMM), and the mangrove planting program with NGO Grow Up Institute (GUI) have contributed positively to advancing the Green Economy and achieving Sustainable Development Goals. This community has successfully created a sense of mutual aid and empowered the community through innovative digital initiatives